The Effect of Cooperative Learning Model STAD Type Based on Mind Mapping toward Students’ Learning Outcomes on Chemical Bond Material in 10th Grade SMA Negeri 1 North Parigi - Nurhijrah Nurhijrah; Paulus H. Abram; Sitti Aminah (Universitas Tadulako, 2020)
This study aimed to describe the effect of cooperative learning model STAD type based on mind mapping toward students’ learning outcomes on chemical bond material in 10th Grade SMA Negeri 1 North Parigi. This type of research was quasi experiment with a non-randomized pretest posttest control group design. Sampling was done based on special considerations (purposive sampling). The sample used in this study were students of class X Science 1 as the experimental class (n = 22) and class X Science 2 as the control class (n = 23). The results of data analysis obtained the average value ( ) of the experimental class was 72.18 with a standard deviation of 13.12, while of the control class was 66.21 with a standard deviation of 10.04. The results of hypothesis testing with one-party t-test statistics (right party) obtained a value of tcount = 6.03 and ttable = 1.68 with a significant level of ( ) = 0.05 and dk = 43. This indicated that H0 was rejected and H1 was accepted so it can be concluded that learning outcomes with cooperative learning model STAD type based mind mapping was higher than the direct learning model on chemical bonding.